2010
DOI: 10.4314/thrb.v12i4.56152
|View full text |Cite
|
Sign up to set email alerts
|

Association of intestinal helminths and P. falciparum infections in co-infected school children in northwest Tanzania

Abstract: Plasmodium falciparum malaria and intestinal helminth infections are among the most common infections in the tropics and they share the same spatial distribution. The objective of this study was to explore the association between infections with intestinal helminths and P. falciparum infection as single helminth infections or co-infections among school children. A cross-sectional study was conducted among (OR= 0.749,, P. falciparum and hookworm (OR= 0.885, In sub-Saharan Africa, the overlapping distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
(7 reference statements)
2
4
1
Order By: Relevance
“…No association was found between malaria infection and S. mansoni infection neither between malaria infection and STH infection. This is in total agreement with previously reported data from Tanzania in 2010 [40].…”
Section: Discussionsupporting
confidence: 94%
“…No association was found between malaria infection and S. mansoni infection neither between malaria infection and STH infection. This is in total agreement with previously reported data from Tanzania in 2010 [40].…”
Section: Discussionsupporting
confidence: 94%
“…While there are hardly any cross-sectional surveys assessing E. vermicularis infections with appropriate diagnostic methods in sub-Saharan Africa, let alone its potential association with malaria, there are multiple studies investigating associations between hookworm and Plasmodium infections. In line with our findings, there are studies that did not find an association between hookworm and Plasmodium infections [ 67 ],[ 68 ]. Other studies, however, indicate significant associations between these infectious diseases [ 38 ],[ 62 ],[ 69 ].…”
Section: Discussionsupporting
confidence: 93%
“…High prevalence of asymptomatic Plasmodium infection was observed 26/385 (6.8%) in this geographical setting; this might be the effect of climate change on highland malaria transmission which is strongly dependent on the temperature, because temperature is known to influence transmission intensity through its effects on the population growth of the mosquito vector and on pathogen development within the vector [ 22 ]. This finding is very low compared to a study conducted on school children in Southwest Cameroon, which reported a prevalence of 44.3%, in Yemen 12.8%, in Mount Cameroon region 87.8%, in Osogbo (Nigeria) 25.6%, and in Tanzania 14% [ 23 – 27 ]. The reasons behind this fact remain to be clarified, but we can speculate that this might be associated with biological variability, such as genetic susceptibility related to the presence of sickle cell trait, beta-thalassaemia, or Duffy blood factor [ 28 , 29 ] and differences in exposure to mosquito bites which are related to the living standard of the community, burden of mosquito vector, type of occupational activity, housing characteristics (e.g., screening, roof materials, and open eaves) [ 29 , 30 ], and the use of selected preventative measures [ 31 ].…”
Section: Discussioncontrasting
confidence: 60%